2020
DOI: 10.1101/2020.05.26.116111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced reproductive success is associated with selective constraint on human genes

Abstract: SummaryGenome-wide sequencing of human populations has revealed substantial variation among genes in the intensity of purifying selection acting on damaging genetic variants. While genes under the strongest selective constraint are highly enriched for Mendelian disorders, most of these genes are not associated with disease and therefore the nature of the selection acting on them is not known. Here we show that genetic variants that damage these genes reduce reproductive success substantially in males but much … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…Gene panel association tests suggest a strong and consistent trend for increasing phenotypic effects with rarer and more damaging variants. Our findings are consistent with similar studies 4,[20][21][22][23][24] showing reduced penetrance of rare damaging variants in monogenic forms of DD in clinically unselected population cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…Gene panel association tests suggest a strong and consistent trend for increasing phenotypic effects with rarer and more damaging variants. Our findings are consistent with similar studies 4,[20][21][22][23][24] showing reduced penetrance of rare damaging variants in monogenic forms of DD in clinically unselected population cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…Admittedly, ancestral claims can be debated and, again, the mechanisms of selection may include those that are not competition-based. A more recent genome-wide association study, for example, found that men's, but not women's, propensity for childlessness was higher in the presence of harmful autosomal mutations (Gardner et al, 2020). These mutations were correlated with lower intelligence and higher incidence of mental illness, and their association with DOMAINS OF FEMALE CHOICE childlessness remained when physiological explanations (e.g., infertility) were ruled out.…”
Section: Evidence From Geneticsmentioning
confidence: 99%
“…Explicitly designing interventions sex-specifically based on these insights might help address stagnating life expectancy and sexual disparities.Sexual dimorphism in lifespan is widely evident, including among humans, contemporaneously and historically 1,2 . Many reasons have been advanced for shorter life expectancy in men than women, from gendered health and health care seeking behavior 3 through sex-specific nutrient metabolism and steroid hormones 4 to sex-specific sexual selection pressures 5,6 , but few of these have been explicitly exploited as a means of promoting healthy aging in both sexes. As the long-term trend of increasing life expectancy in the West now appears to be stagnating 7 , reconsidering overlooked targets and their implications for the design of interventions might bear consideration.An obvious modifiable difference between men and women is levels of sex hormones.…”
mentioning
confidence: 99%